﻿Anti-inflammatory activity of Sabicea brevipes Wernharm (Rubiaceae) - Emmanuel Ifeanyi Attah; Samson Chibuzo Ugwuagbo; Sampath Chinnam; Fabian Ifeanyi Eze; Charles Okeke Nnadi; Matthias Onyebuchi Agbo; Wilfred Obonga; Mithun Rudrapal; Sanjay G. Walode; Aatika Nizam; Ranjan Kumar Sahoo; Atul R. Bendale; et al. (Pensoft Publishers, 2022)
Over the years, medicinal plants have been employed in the treatment of inflammation and related ailments. This study evaluated the anti-inflammatory potential of the aerial parts of S. brevipes. The extracts and fractions were further evaluated for anti-inflammatory activity in carrageenan-induced rat model at varying doses (200 and 400 mg/kg doses, orally) for 5 h of treatment. The result of the phytochemical screening showed the presence of alkaloids, terpenoids, glycosides, flavonoids and tannins in the aerial parts of the plant. The in vivo anti-inflammatory study exhibited inhibition of 42% and 44%, 47% and 36%, 33% and 31%, and 43% and 42% for methanol extract n-hexane fraction, ethyl acetate fraction, and methanol fraction, at 200 and 400 mg/kg doses, respectively. The positive control (diclofenac sodium) showed an inhibition value of 51% at 5 mg/kg dose. Finally, it is concluded that S. brevipes possesses anti-inflammatory potential which validates the enthnomedicinal claim of the plant.